Reappraisal of Hawaiian species of Corallianassa Manning, 1987 (Crustacea: Axiidea: Callichiridae) - Poore, Gary C. B.; Longenecker, Ken; Tudge, Christopher C. (Zootaxa, 2023)
Four species of the callichirid ghost shrimp genus Corallianassa Manning, 1987 are recognised in Hawaii based on evidence from morphology and the CO1 gene. Corallianassa borradailei (De Man, 1928) is a widespread Indo-West Pacific species now confirmed for Hawaii. Corallianassa lanceolata Edmondson, 1944 is an endemic species similar to C. assimilis (De Man, 1928) from Indonesia and Guam. Corallianassa martensi (Miers, 1884) is also a widespread Indo-West Pacific species. Callianassa (Callichirus) winslowi Edmondson, 1944 (Hawaii), Callianassa (Callichirus) nakasonei Sakai, 1967 (Japan) and Callianassa haswelli Poore & Griffin, 1979 (Australia) are treated as junior subjective synonyms of C. martensi. Callianassa (Callichirus) oahuensis Edmondson, 1944, long treated as a junior synonym of C. borradailei, is revived as a valid species of Corallianassa. The four species differ in the shape and dorsal setae of the telson, the extent of the carina along the upper margin of the major cheliped palm, the attitude of the rostrum, and the shape of the maxilliped 3.